An African orchestra in Ghana - Osafo, F. Onwona (International Library of African Music, 1957)
In Ghana, the string section of the African orchestra consists mainly of the native guitars and violins. They are of different shapes and sizes, and are generally made of wood, large calabashes or gourds, and animal skins or leather. The strings, which may be between four and six in number, are made from the sinews of a sheep, cow, cat or any other domestic or bush animal suitable for the purpose, although wire is sometimes used. Animal sinew is normally used for the bows of the native violins. The guitars are plucked and the violins are bowed, but on rare occasions they, also, are plucked. The tone quality of these two instruments vary. Some are calm, ethereal and penetrating, some are warm, rich and expressive, and others are nasal, harsh and serious.
Keywords: Musical instruments; African Music; Ghana; Orchestra